Life in conflict: Characteristics of Depression in Kashmir - Amin, Syed; Khan, A.W. (International Journal of Health Sciences, 2009)
Background: Mental, physical and social health, are vital strands of life that are closely interwoven and deeply interdependent. Mental disorders affect people of all countries and societies, individuals at all ages, women and men, the rich and the poor, from urban and rural environments. Depression is more likely following particular classes of experience – those involving conflict, disruption, losses and experiences of humiliation or entrapment. Many people living amidst the rages of conflict suffer from posttraumatic stress disorder. Objective: To determine the characteristics of depression in the population in Kashmir where a low-intensity-conflict has been going on for the last seventeen years. Methods: The non-combatant civilian population was surveyed. The Centre for Epidemiological Studies Depression (CES-D) Scale was used to measure symptoms of depression in community populations. Results: Due to continuing conflict in Kashmir during the last 18 years there has been a phenomenal increase in psychiatric morbidity. The results reveal that the prevalence of depression is 55.72%. The prevalence is highest (66.67%) in the 15 to 25 years age group, followed by 65.33% in the 26 to 35 years age group. The difference in the prevalence of depression among males and females is significant. Depression is much higher in rural areas (84.73%) as compared to urban areas (15.26%). In rural areas the prevalence of depression among females is higher (93.10 %) as compared to males (6.8%). Conclusion: Mental health is an integral part of overall health and quality of life. Effective evidence-based programs and policies are available to promote mental health, enhance resilience, reduce risk factors, increase protective factors, and prevent mental and behavioural disorders. Innovative community-based health programmes which are culturally and gender appropriate and reaches out to all segments of the population need to be developed. Substantial and sustainable improvements can be achieved only when a comprehensive strategy for mental health which incorporates both prevention and care elements is adopted.